Comparative Assessment of Pesticide Residues in Groundnuts Sold in Selected Markets in Port Harcourt Metropolis, Rivers State, Nigeria - Wokoma, Okorinama Abarinka Francis; Ibhadon, Patience Egbeziemin; Mmom, ThankGod Chikwere (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
In this study, pesticide residues [pyrimethanil, Diazinon, Malathion, Chlorpyrifos, Dichlorodiphenyldichloroethane (DDD), Dichlorodiphenyltrichloroethane (DDT), and Dichlorodiphenyldichloroethylene (DDE)] were investigated in groundnut (Arachis hypogaea L.) samples from two prominent markets [the Mile three (3) Market, and Sagana Market] in Port Harcourt metropolis, Rivers State, Nigeria. Fresh and roasted samples were bought and analysed from both markets. The same parameters were also analysed in “homemade” samples. Samples were transported to the laboratory in well tagged sterile polythene bags for analysis. Characterisation was done using the MassHunter quantitative analysis. Thereafter, the GC-MS machine was used for detection of pesticide residues. Findings from this study revealed the presence of pesticide residues in all the groundnut samples analysed. Homemade samples had relatively low amounts forDiazinon(0.0966mg/kg), Malathion (1.0636 mg/kg) and Chlorpyrifos (0.0095 mg/kg) that were within the available FAO/WHO maximum residues limits (MRLs) for groundnut (legume vegetables) unlike the samples from both Sangana and Mile 3 Markets. The concentration of investigated pesticide residues followed the order, DDE>DDT >DDD> Malathion > Diazinon > Pyrimethanil, with DDE measuring as high as 1127.785mg/kg in fresh groundnut sample from a location in Mile 3 Market. Results revealed pesticides in various samples had their unique peculiarities. Further studies to investigate the causes behind these peculiarities could reveal how pesticides interact within distinct environments and/or market conditions. The detection of some pesticides above permissible limits call for more studies to forestall the incidence of toxicity from the ingestion of pesticides contaminated food substances, including groundnuts.